Relevansi Kurikulum Hospitality Politeknik Pariwisata Makassar terhadap Restoran di Sulawesi Selatan - Muhammad Arifin; Muh. Zainuddin Badollahi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
This study aims to see where the relevance of the spatial management study program curriculum to restaurants in South Sulawesi specifically chooses 3 regencies/cities that have a 3A visit level and tourism concept. By using quantitative descriptive. Based on research results found in the existing curriculum relevant to restaurants this can be used from the absorption of alumni who work in the hotel and restaurant sector as much as 98.94%. Besides that the waiting time for alumni to get an average job is 3-6 months.